Valorization of wheat bran for cost-effective production of cellulolytic enzymes by Aspergillus fumigatus SKH2 and utilization of the enzyme cocktail for saccharification of lignocellulosic biomass - Jena, Harekrushna; Haider, Suman Kumar; Soren, Jyoti Prakash; Takó, Miklós; Mondal, Keshab Chandra (Acta Biologica Szegediensis, 2016)
Production of cellulolytic enzymes like CMCase (endoglucanase), FPase, and xylanase by Aspergillus fumigatus SKH2 under solid state fermentation was carried out employing wheat bran as low cost substrate. Fermentation time, medium pH and incubation temperature were optimized at 48 h, pH 5.0 and 35 °C, respectively. At optimized state, CMCase (endoglucanase), FPase and xylanase of 826, 102 and 1130 U/gds yield was noticed, respectively. Crude enzyme cocktail was assayed at varied pH and temperature, and pH 5.0 and 35 °C were proved to be optimal for the studied enzyme activities. Fourier transform infrared spectroscopic FTIR analysis attested that NaOH was a good delignifying agent for sugarcane bagasse and grass Aristida sp., which enhanced subsequent saccharification efficiency of cellulolytic enzyme cocktail. By correlating FTIR analysis with saccharification profile it was found that highest saccharification was achieved after 16 h and 48 h after treating with 1M and 3M NaOH for sugarcane bagasse and Aristida sp., respectively. The present investigation validates eco-friendly and cost effective production of A. fumigatus SKH2 cellulolytic enzyme cocktail using agricultural waste materials, and subsequent application of this cellulase mixture for saccharification of lignocellulosic biomass, which collectively endorse the employment of the bioprocess to produce biofuel in future.